Solute Leaching in Effluent-irrigated Clay Soil in South-eastern Australia - Hooda, Anil K.; Weston, Chris; Hooda, Neeta (Indian Forester, 2005)
Leaching of nitrate-N to groundwater in excess of safe drinking water standards is the main concern with respect to the fate of nitrogen in effluent irrigation. This study mainly examines the NO3-N in soil solutions that percolates through the soil profile in a trial established at Shepparton (Australia) with high density plantations of Eucalyptus globulus coppiced at short rotations to maximize the removal of nitrogen from thc applied secondary treated effluent on clayey soils. The NO3-N concentrations in soil solutions in eoppiced treatments 0.81.8.2 mg L-1) at 40 and 100 em depths remained below the safe permissible limits for the drinking water during the first year after coppicing of three old plants. These NO3-N concentrations in soil solutions in coppiced treatments decreased further during the second year after coppicing as the uptake by the plants increased. In contrast the NO3-N concentrations at 40 and 100 cm depths in un.coppiced treatments i.e. 4 and 5 year old plants were higher as the uptake by the plants decreased. The stand density of 1333 and 2667 plants per hectare was not found to have significant effect on these NO3-N concentrations in soil solutions. In contrast, the method of effluent application and soil factors affected the NO3-N concentrationsin soil solutions. Compared to natural forests, the nitrate was not the dominant solution anion in soils irrigated with alkaline effluent where chloride was the dominant anion.